Physical accessibility of primary care facilities for people with disabilities: a cross-sectional survey in 31 countries - Peter P. Groenewegen; Madelon Kroneman; Peter Spreeuwenberg (BMC, 2021)
Abstract Background Primary care is the first point of care, also for people with disabilities. The accessibility of primary care facilities is therefore very important. In this study we analysed comparative data on physical accessibility of general practices (GP practices) in 31 (mainly) European countries. Methods We used data from the QUALICOPC study, conducted in 2011 among GPs in 34 (mainly European) countries and constructed a physical accessibility scale. We applied multilevel analysis to assess the differences between and within countries and to test hypotheses, related to characteristics of the practices and of the countries. Results We found large differences between countries and a strong clustering of physical accessibility within countries. Physical accessibility was negatively related to the age of the GPs, and was less in single-handed and in inner city practices. Of the country variables only the length of the period of social democratic government participation during the previous decades was positively related to physical accessibility. Conclusion A large share of the variation in physical accessibility of GP practices was on the level of countries. This means that national policies can be used to increase physical accessibility of GP practices.